Toward universal influenza virus vaccines: from natural infection to vaccination strategy. (August 2018) - Zhao, Chen; Xu, Jianqing
Highlights: Recent development of HA stalk-based universal influenza vaccines is outlined. Special focus was placed on group 2 stalk-based vaccine against H7N9 virus. The group 2 stalk might elicit a broader Ab response than group 1 stalk. Many group 2 stalk-induced Abs are non-neutralizing but protective in vivo . Development of cross-group stalk antibodies may require special prime-boost mode. Abstract : Conceptually, a universal influenza vaccine should elicit broadly protective antibody responses targeting highly conserved epitope(s) shared by various virus strains. Strategically directing antibody immunity to the conserved hemagglutinin stalk has recently emerged as a promising approach that is substantiated by the identification of naturally occurring, stalk-reactive human antibodies capable of conferring broad protection against influenza virus challenge in animal models. Despite all the advancements, future realization of this strategy still faces many challenges, particularly whether it is able to induce enough of cross-reactive antibody response to protect against pandemic viruses. In this respect, recent in-depth dissections of human immune responses to H7N9 virus and vaccination provide much-needed new insights.